Genetics of co-developing conduct and emotional problems during childhood and adolescence. (July 2018) - Hannigan, Laurie; Pingault, Jean-Baptiste; Krapohl, Eva; McAdams, Tom; Rijsdijk, Frühling; Eley, Thalia
Abstract Common genetic influences offer a partial explanation for comorbidity between different psychiatric disorders1–3 . However, the genetics underlying co-development—the cross-domain co-occurrence of patterns of change over time—of psychiatric symptoms during childhood and adolescence has not been well explored. Here, we show genetic influence on joint symptom trajectories of parent-reported conduct and emotional problems (overallN  = 15, 082) across development (4–16 years) using both twin- and genome-wide polygenic score analyses (genotypedN  = 2, 610). Specifically, we found seven joint symptom trajectories, including two characterized by jointly stable and jointly increasing symptoms of conduct and emotional problems, respectively (7.3% of the sample, collectively). Twin modelling analyses revealed substantial genetic influence on trajectories (heritability estimates range of 0.41–0.78). Furthermore, individuals' risk of being classified in the most symptomatic trajectory classes was significantly predicted by polygenic scores for years-of-education-associated alleles and depressive symptoms-associated alleles. Complementary analyses of child self-reported symptoms across late childhood and early adolescence yielded broadly similar results. Taken together, our results indicate that genetic factors are involved in the co-development of conduct and emotional problems across childhood and adolescence, and that individuals with co-developing symptoms across multiple domains may represent a clinical subgroup characterized by increased levels of genetic risk. Analyses of twin and genomic data show a significant influence of genetic factors on the co-development of conduct and emotional problems from childhood to adolescence. Those with co-developing symptoms may represent a clinical subgroup with higher genetic risk.